Pengembangan Kapasitas Ekonomi Berbasis Masyarakat Di Desa Wisata Cibuntu, Indonesia - Asep Syaiful Bahri; Rianto Suyatno (Indonesian Journal of Cultural and Community Development, 2018)
The process of planning and decision making in the development program for this is oftenly done by top-down. Most often society is not given a choice and an opportunity to provide input. Sometimes government assistance creates dependency, which in turn would create trouble than help. The purpose of this study was to illustrate the potential of tourism and economic potential in the Cibuntu village as well as to determine the model to improve the local economy based on tourism. Samples are some families in the Cibuntu village. The results of this study indicate that the tourism and economic potential are very diverse and can support tourism activities and for the community-based model of economic improvement which can be implemented is culinary-based, homestay based and craft-based.